Partial actions and automata - Dokuchaev, M.; Novikov, B.; Zholtkevych, G. (Algebra and Discrete Mathematics, 2011)
We use the notion of a partial action of a monoid to introduce a generalization of automata, which we call ``a preautomaton''. We study properties of preautomata and of languages recognized by preautomata.